(untitled) (Medical Forum Monthly, 2022)
Objective: To estimate the frequency of aspiration pneumonia in post stroke patients with the use of dysphagia screen and to analyze the associated risk factors. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Ayub teaching hospital, Abbottabad from May, 2018 to October, 2018. Materials and Methods: The study included patients diagnosed with hemorrhagic and ischemic strokes, who developed dysphagia later. The studied population included samples from both sexes (males and females) with the age group of 35 and above. Detailed history and examination findings were recorded, CT scan brain was performed to confirm the diagnosis of stroke. Chest x-ray and complete blood count were performed for the patients who developed signs and symptoms of pneumonia. Results: A total of 100 cases that developed post-stroke dysphagia were analyzed for the study. Results revealed that 66% of the patients were diagnosed with ischemic stroke, whereas, 34% were diagnosed hemorrhagic stroke. 54% of patients developed aspiration pneumonia during hospital stay. Among patients with aspiration pneumonia 88% (48) had dysphagia. Conclusion: A high frequency of occurrence of aspiration pneumonia in post stroke patients is observed. Therefore, early assessment of dysphagia before oral intake in all stroke patients is advised to prevent aspiration pneumonia.